Design, simulation, and manufacturing of analyzer optical cell for detection and measurement of injectable odorant at pressure reduction stations - Hamideh Samari Jahromi; Mohsen Abdollahi; Azardokht Mazaheri; Soleyman Mantaghi; Amirhomayoon Rezaeian; Ali Sadouni; Hamidreza Naseri; Kioumars Taheri; Fariborz Hashemipour; Foad Hamzavi; Abdolsamad Naseh (Heliyon)
The absence of a mercaptan compounds analyzer in natural gas pressure reduction stations (PRS) odorizer leads to inaccuracies in the injection dosage, often resulting in quantities beyond standard limits and consequently increasing odorant consumption. Insufficient odorant levels in natural gas can pose safety risks to consumers, as the gas may become odorless at the end of the pipeline. Therefore, accurate determination of the concentration of key odorant compounds in natural gas can reduce both costs and environmental risks. In this study, a hybrid UV-IR analyzer for detecting key odorant compounds was designed and developed. Initially, regional conditions were examined, and various natural gas and odorant samples were analyzed to identify compound percentages, which were then used to prepare calibration gas cylinders. Based on the results of simulated conditions, the analyzer's structure was designed, and technical specifications of components were determined. The analyzer consists of mechanical and optoelectronic units, connected via fiber optics. Subsequently, an optical cell was designed and manufactured, and the performance of the analyzer's components was evaluated in laboratory testing systems. This device can measure two key compounds, tert-butyl mercaptan and isopropyl mercaptan, separately, simultaneously, or in mixtures, making it comparable to an online gas chromatograph (GC). Installing this analyzer in PRSs enables precise adjustment of odorant injection dosages based on the analyzer's real-time results.